FAKTOR YANG BERPENGARUH TERHADAP KEPUTUSAN PEMBELIAN BUKU UMUM PADA PT TIGA SERANGKAI INTERNATIONAL GENERAL BOOK DIVISION - Sunarso, Mustaqim & (Universitas Slamet Riyadi, 2012)
ABSTRACT This study aims to analyze the significance of the effect of pricing, promotion, and quality products to the general ledger product purchasing decisions on PT Tiga Serangkai International General Book Division. The population in this study is that consumers generally buy books published by PT. Tiga Serangkai inÂ bookstore Gramedia and Togamas in the city of Yogyakarta, Solo and Semarang. Samples were taken by 100 respondents. The results showed that prices and promotions significantly influence the decision of the general purchase of books, is the quality of the products had no significant effect. Keywords: Bookstore, pricing, promotion, quality, purchasing decisions.